Sistem Manajemen Energi Hibrida pada Sumber Energi Baterai-Superkapasitor Berbasis Automatic Switching - Mubarak, Bagja Rahmat; Prihtiadi, Hafizh; Diantoro, Markus; Harly, Muchammad; Afrianda, Teguh (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
This research develops an automatic switching-based hybrid energy management system that integrates batteries and supercapacitors to improve power distribution efficiency in electric vehicles. The system is controlled by a microcontroller that monitors the current in real-time and activates the supercapacitor line when the current exceeds 10 A. The switching circuit uses IR2110 and IRFP4568 MOSFETs. Tests were conducted in three scenarios: battery only, hybrid without load, and hybrid with load. In the no-load condition, the supercapacitor produced a peak current of 18.23 A and an average of 5.73 A, while the battery recorded an average current of 8.52 A. In the loaded condition, the supercapacitor peak current reached 20.87 A, with an average of 10.82 A, while the battery was 11.95 A. The total energy increased from 55022.25 J (battery only) to 92000.76 J (no-load) and 147019.09 J (with load). The efficiency also increased from 1.0% to 2.4% in the hybrid configuration. The system showed a stable energy conversion efficiency of 95% under both hybrid conditions. These results prove that automatic integration of supercapacitors can improve system efficiency and performance without the complexity of control algorithms.